KEMAMPUAN MAHASISWA PROGRAM STUDI BELANDA SEMESTER KEEMPAT TAHUN AJARAN 2024/2025 DALAM MENYUSUN URUTAN ELEMEN REST - Batista, Daniel Renanda; Gustinelly, Eliza (Multikultura, 2026)
The construction of syntactically correct sentences plays an important role in conveying messages clearly and accurately during communication. Therefore, this study discusses the ability of fourth-semester students of the Dutch Studies Program at Universitas Indonesia in the 2024/2025 academic year to arrange rest elements, such as direct objects, indirect objects, adverbs of time, frequency, quantity, instrument, and place. The study focuses on syntax, and using a quantitative descriptive method to analyze students' ability to arrange rest elements according to syntactic rules. The data used in this study were obtained from 30 students who completed 25 questions containing scrambled words. The students were asked to rearrange the words into the correct rest elements. The results show that students' ability to arrange the rest elements is moderate, with a correct answer percentage of 76.80%. This indicates that more than half of the students have a good understanding of the structure of rest, others still face difficulties in arranging the rest.